2006
DOI: 10.1001/jama.295.23.joc60074
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Tamoxifen vs Raloxifene on the Risk of Developing Invasive Breast Cancer and Other Disease Outcomes<SUBTITLE>The NSABP Study of Tamoxifen and Raloxifene (STAR) P-2 Trial</SUBTITLE>

Abstract: clinicaltrials.gov Identifier: NCT00003906.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
799
3
27

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,553 publications
(842 citation statements)
references
References 44 publications
13
799
3
27
Order By: Relevance
“…Vogel et al [35] observed a significant reduction of incidence of contralateral primary breast cancer among women receiving adjuvant hormonal therapy. Adjuvant hormonal therapy also reported to reduce the incidence of BBC by 40% in both ER positive and ER negative patients [36].…”
Section: Discussionmentioning
confidence: 98%
“…Vogel et al [35] observed a significant reduction of incidence of contralateral primary breast cancer among women receiving adjuvant hormonal therapy. Adjuvant hormonal therapy also reported to reduce the incidence of BBC by 40% in both ER positive and ER negative patients [36].…”
Section: Discussionmentioning
confidence: 98%
“…The most important side effects reported in patients undergoing long-term tamoxifen treatment consist of visual impairment, cataracts, 61 and risk of thromboembolic events. 62,63 Tamoxifen has weak estrogenic properties that can induce endometrial cell proliferation and, consequently, endometrial cancer. 64 In addition, tamoxifen seems to increase the risk of radiation-induced lung and skin fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Raloxifene and tamoxifen have been shown to cut down the risk of estrogenreceptor positive breast cancers by as much as 50% (Vogel et al 2006). Tamoxifen, a selective estrogen receptor modulator, has demonstrated benefit when used alone as well as in combination with chemotherapy to treat advanced breast cancer.…”
Section: Estrogen Signalingmentioning
confidence: 99%